Gender-based and intersectional violence in migration and refugee contexts: a contextual global approach - Tastsoglou, Evangelia (International sociology, 2025)
Gender-based violence is a major infringement of women’s human rights, and an obstacle to sustainable development as set out in the Sustainable Development Goals. In this article, we explore both the processes and findings of our international comparative project on gender-based violence in migration contexts. Our research takes a feminist, intersectional, collaborative, and contextual approach to understand gender-based violence in the context of migration, analysing the ways in which discriminations and inequalities based on gender, race, nationality, ethnicity, sexual orientation, gender identity and age, interact to make certain women more vulnerable to gender-based violence. While we start from the lived experiences of women and persons working with them, we engage meso- and macro-level analyses of border practices, reception conditions and policy implementation, policies and legal systems that exacerbate their plight in order to understand the underlying dynamics that re(produce) patterns of violence. Our project shows the need for situated and contextual analyses of gender-based violence in national contents, but also the global rootedness of gender-based violence, and the key role of States in creating the structural conditions for the production of gender-based violence in migration contexts.